Multimode tumor ablation therapy induced different diffusion and microvasculature related parameters change on functional magnetic resonance imaging compared to radiofrequency ablation in liver tumor: An observational study. Issue 26 (26th June 2020) - Zhang, Guangyuan; Li, Wentao; Wang, Guangzhi; He, Xinhong; Xu, Lichao; Wang, Shengping; Peng, Weijun
Abstract : Abstract: To explore different posttreatment changes between multimode tumor ablation therapy (MTAT) and radiofrequency ablation (RFA) using intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) and diffusion kurtosis imaging (DKI) in patients with hepatic malignancies. Eighty - seven patients with one hundred and twenty eight hepatic lesions receiving MTAT or RFA underwent IVIM-DWI and DKI before and after treatment. The mean value of apparent diffusion coefficient (ADC), IVIM-DWI parameters, including true diffusion coefficient (D), pseudo-diffusion coefficient (DP), perfusion fraction (f), and DKI parameters including diffusion coefficient (DK), apparent diffusional kurtosis (K) were retrospectively compared prior to and following treatment as well as between treatment groups. The degree of parameters change after ablation was compared between 2 treatment modalities. The mean value of ADC, D, and DK increased while f, and K decreased significantly in MTAT group. In RFA group, just ADC and K showed significantly change following treatment. The ADC and D value were higher in MTAT group than in RFA group 1 month after treatment. While f was lower in MTAT group after treatment compared with RFA group. The ADC, D and DK increased (21.89 ± 24.95% versus 8.76 ± 19.72%, P = .04 for ADC, 33.78 ± 54.01% versus 7.91 ± 25.16%, P = .03 for D, 25.91 ± 36.28% versus 1.75 ± 46.42%, P = .01 for DK) while f declined (-32.62 ± 41.48% versus 6.51 ± 44.16%, P < .001) more in MTAT group. The MTAT induced different posttreatment changes on water molecule diffusion and microvasculature related functional MR parameters compared to RFA in patients with liver tumors. Abstract : Supplemental Digital Content is available in the text